The lncRNA GAS5 upregulates ANXA2 to mediate the macrophage inflammatory response during atherosclerosis development - Xue, Yuzhou; Hu, Yu; Yu, Shikai; Zhu, Wenyan; Liu, Lin; Luo, Minghao; Luo, Suxin; Shen, Jian; Huang, Longxiang; Liu, Jie; Lv, Dingyi; Zhang, Wenming; et al. (Heliyon, 2024)
Inflammatory macrophages play a crucial role in atherosclerosis development. The long non-coding RNA growth arrest-specific 5 (GAS5) regulates THP-1 macrophage inflammation by sponging microRNAs. The purpose of this study was to investigate the regulatory mechanism of GAS5 in atherosclerosis development. GSE40231, GSE21545, and GSE28829 datasets from the Gene Expression Omnibus database were integrated after adjusting for batch effect. Differential analysis was performed on the integrated dataset and validated using the Genotype-Tissue Expression and GSE57691 datasets. Potential biological functions of GAS5 and annexin A2 (ANXA2) were identified using gene set enrichment analysis (GSEA). ssGSEA, CIBERSORTx, and ImmuCellAI algorithms were used to identify immune infiltration in plaque samples. GAS5 and ANXA2 expression levels in RAW264.7 cells treated with oxidized low-density lipoprotein (ox-LDL) were measured by qRT-PCR and Western blot. Small interfering and short hairpin RNA were used to silence GAS5 expression. Plasmids of ANXA2 were used to establish ANXA2 overexpression. Apoptosis and inflammatory markers in macrophages were detected by Western blot. Aortic samples from APOE−/− mice were collected to validate the expression of GAS5 and ANXA2. GAS5 expression was significantly increased during atherosclerosis. GAS5 expression was positively correlated with macrophage activation and ANXA2 expression in plaques. Furthermore, ANXA2 upregulation was also related to the activation of macrophage. GSEA indicated similar biological functions for GAS5 and ANXA2 in plaques. Moreover, in vitro experiments showed that both GAS5 and ANXA2 contributed to macrophage apoptosis and inflammation. Rescue assays revealed that the inflammatory effects of GAS5 on macrophages were ANXA2-dependent. In vivo experiments confirmed the highly expression of Gas5 and Anxa2 in the plaque group. We identified the atherogenic roles of GAS5 and ANXA2 in the inflammatory response of macrophages. The inflammatory response in ox-LDL-treated macrophages was found to be mediated by GAS5-ANXA2 regulation, opening new avenues for atherosclerosis therapy.